Diskurzivne prvine v izbranih Trubarjevih predgovorih in pismih - Bošnjak, Blanka (Slavia Centralis, 2008)
The thesis of this paper is that, by means of analyzing Trubar's selected prologues and correspondence, the following regularity is evident from the viewpoint of discourse theory: in Trubar's time discourse diversity tended to have some common starting points.
Keywords: 16.st.; diskurz; protestantizem; slovenščina